Perencanaan Audit Laporan Keuangan Berdasarkan Standar Profesional Akuntan Publik pada Kantor Akuntan Publik di Provinsi Sulawesi Selatan - Masnawaty Sangkala; Hajrah Hamzah (Seminar Nasional LP2M UNM, 2022)
Abstrak. This study aims to determine the planning procedures for auditing financial statements at KAPs in South Sulawesi Province. The variable that is the focus of this study is the Financial Report Audit Planning Procedures at KAPs in South Sulawesi Province. The data collection method used is documentation. The data analysis was carried out using descriptive analysis. The results of this study indicate that the planning procedures for auditing financial statements at KAPs in South Sulawesi Province are the same as those proposed by Munawir Kata Kunci: Financial Statement Audit Planning Procedures